1981
DOI: 10.1002/1097-0142(19810715)48:2<257::aid-cncr2820480209>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Melanotic neuroectodermal tumor of infancy: An ultrastructural study, literature review, and reevaluation

Abstract: Two cases of melanotic neuroectodermal tumor of infancy were examined by electron microscopy and an extensive review of the literature was performed. Ultrastructural examination revealed several features not previously described for this lesion. Three different types of melanin granule formation were observed, many cells had a single cilium, and cell junctions of the "close" or "modified-tight" type were seen, but no desmosomes were found. The morphologic data were consistent with the concept that the tumor ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
2
5

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(114 citation statements)
references
References 83 publications
2
105
2
5
Order By: Relevance
“…Therefore, one would expect other markers for neural tissue, including neurofilaments or glial filaments, the intermediate filament types present in neurons or astrocytes, respectively, to be present in these cells (6)(7)(8). In electron microscopic studies (9), intermediate-sized filaments (10-nm thick) have been reported for melanin-forming neuroectodermal tumor cells and have been referred to as tonofilaments (10) or neurofilaments (11). In general, the type of intermediate-sized filaments present in specific cell types seems to depend primarily on their differentiation and embryological origin (4).…”
Section: Introductionsupporting
confidence: 92%
“…Therefore, one would expect other markers for neural tissue, including neurofilaments or glial filaments, the intermediate filament types present in neurons or astrocytes, respectively, to be present in these cells (6)(7)(8). In electron microscopic studies (9), intermediate-sized filaments (10-nm thick) have been reported for melanin-forming neuroectodermal tumor cells and have been referred to as tonofilaments (10) or neurofilaments (11). In general, the type of intermediate-sized filaments present in specific cell types seems to depend primarily on their differentiation and embryological origin (4).…”
Section: Introductionsupporting
confidence: 92%
“…Given the benign nature of most tumours, there has been some controversy over the optimal surgical management and necessity of adequate margins. Views range from conservative enucleation, to curettage of adjacent tissue, to recommended margins of up to 5 mm (2,18,20,36,37). Efforts should be directed toward the preservation of vital structures and organs (38).…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Ninety two percent of tumours were in the head and neck area of which 2/3rd were present in maxilla. Ninety two per cent of cases occured in children Icss than I year of age [4]. The nature of these lesions is uncertain and had the features of both a hamartoma and a true neoplasm with debatable histogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is rare, usually benign , asymptomatic pigmented lesion that arises in the maxilla of children below I year of age [1,2] . However, the tumor has also been reported in adults [3], in sites other than maxilla [4] and occasionally, it is characterized by a malignant behaviour [5]. We present a case ofmelanotic progonoma of maxilla in infancy with review of literature.…”
Section: Introductionmentioning
confidence: 89%